Strategi Pemasaran Digital Dalam Meningkatkan Penjualan Pada Toko Saleem Byroxy Kelurahan Sungai Asam Kecamatan Pasar Jambi Kota Jambi - Sahrul Ihsan; Rafidah Rafidah; Dessy Anggraini (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2026)
This study aims to analyze the digital marketing strategies implemented by Saleem Byroxy Store, located in Sungai Asam Village, Pasar Jambi District, Jambi City, and to examine their contribution to improving sales performance. This research employed a descriptive qualitative method with a case study approach. Data were collected through direct observation, in-depth interviews with the store owner, manager, employees, and customers, as well as documentation. The data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings indicate that Saleem Byroxy Store has implemented five integrated digital marketing strategies: social media marketing (Instagram, TikTok, and WhatsApp Business), partnerships with online food delivery platforms (GrabFood, GoFood, ShopeeFood, and Maxim Food), digital promotions and discount programs, attractive visual content management, and the application of the digital marketing mix (4Ps). These strategies have successfully expanded market reach, strengthened customer engagement and loyalty, and contributed to sales growth, as reflected in a 31% increase in annual revenue in 2022 and a 12.5% increase in 2023. However, annual revenue declined by 22% in 2024, indicating that the effectiveness of digital marketing was still constrained by limited digital marketing competencies, suboptimal use of data analytics, and fluctuating market demand. The study concludes that the success of digital marketing depends not only on the adoption of digital platforms but also on the consistent integration of multiple marketing strategies, human resource capability development, and data-driven marketing evaluation to achieve sustainable sales growth.